2009
DOI: 10.1016/j.matlet.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of processing parameters on the ultrasonic degassing of molten AlSi9Cu3 aluminium alloy

Abstract: The effect of high intensity ultrasound on the degassing of AlSi9Cu3 alloy using the novel MMM (Multi-frequency Multimode Modulated) technology was studied. Different ultrasonic parameters (power and frequency), melt temperature and processing times were tested and their influence on the degassing efficiency evaluated. RPT (Reduced Pressure Test) was used to evaluate the hydrogen content in the alloys and the samples porosity level and density. For the experimental conditions used in this research, it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…The degassing effect is mainly related to the ultrasonic power and melt temperature [12]. Owing to the excellent effect of ultrasound on the microstructure in the casting field, many scholars have tried to apply ultrasound in the course of TIG welding.…”
Section: Introductionmentioning
confidence: 99%
“…The degassing effect is mainly related to the ultrasonic power and melt temperature [12]. Owing to the excellent effect of ultrasound on the microstructure in the casting field, many scholars have tried to apply ultrasound in the course of TIG welding.…”
Section: Introductionmentioning
confidence: 99%
“…In metal casting, the ultrasonic vibration (USV) provides multiple significant effects such as degassing [44][45][46][47], refining, and modifying the microstructures [48][49][50][51]. Using USV in brazing is an attractive assisting tool [37][38][39][52][53][54][55][56][57][58]; however, studying the combined effects of USV with the technological parameters of brazing process and developing a joint interface more compatible with the USV have not yet received an adequate attention.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Haberl et al [35] who reported almost 50% reduction in number density of pores in RPT samples after degassing. Although it is well known that degassing reduces the hydrogen content, the main contribution of degassing is considered to be the floatation of bifilms to the melt surface [14,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%